Sinemada entropi : post-sinematik dönemde eleştirel zaman kavramı - Sümer, Murat Deniz (My University, 2023)
Sinema aygıtından saniyede çoklu kare geçişiyle teknolojik bir işlevin fark edilmesini zaman sağlamıştır. Üstelik hem bilinç düzeyinde algılanan zamanı hem de mekanik işleyişte görüntülerin zaman kavramıyla ölçümlenmesini ortaya çıkaran sinemasal zaman, yüzyılı aşkın sürede sanat, bilim ve teknolojinin olanaklarıyla bir anlatım dili oluşturmuştur. Böylece, hayata öykünen karelere akışkan zaman boyutu eklenmiş ve sinemasal evren doğmuştur. Öznel zaman, sinemada izleyicinin bilincine anlam yerleştirme devinimini ve duyusal yanılsamayı yükler. Yapıtın akışkanlığını kontrol eden mekanik unsur ise anlatımın hareketli algılanmasını sağlayan zamandır. Amaç ve yöntemi yansıtması için yapımı gerçekleştirilen “…ilk ve son nefeste zaman…” kurmaca filmi, zamanın tanıklığına bağlı gelişmelerle ortaya çıkan teknolojilerdeki yeniliklerin insanlığın geleceğini tehdit ettiği yönündeki bir öngörüye dayalıdır. Filmin lirik yaklaşımıyla yorumlanan sorunsal, insan eliyle geliştirilen teknolojilerin rol aldığı zaman döngüsünde soyu ve fonksiyonu tükenen canlının da yine insan olduğunun vurgulanmasıdır. Hastane sahnesinde kardiyografik çizelge ve ölümün düz çizgisi, yiyecek kıtlığı yaşayan canlıların çaresizliği, denizlerde müsilaj gibi zamana bağlı anlam yerleştirme etkileri filmin taşıyıcı eksenini oluşturan metaforik biçemdir. Küresel sistemin uç birimlerinde olsak da üzerinde bulunduğumuz alegorik evrensel platform ağında sinema için önemini yitirmeyen tek varoluş aracı görece nesnellikteki eleştirel zaman algısıdır. Yaşadığımız sisteme güçlü zamansal boyutlar veren çok katmanlı süreçlerin dünyası sinema, eğer teknolojik zaman algısını değiştirdiyse; temsilin zamansallığını düşünmek de zor olacaktır. Özetle sinemada zaman, doğanın ekolojik yıkımına tanık olmaktır. Bu nedenle gezegenin tükenişe doğru sürüklenmesinde ortaya çıkan düzensiz enerjinin hayatın her alanına yayılmasını “Sinemada Entropi” olarak ifade etmek istedim. Çünkü elde ettiğim bulgular sinema için zaman konusunda yeni önermeleri kuramlaştırmalı ve yeni düşüncelere yol açmalıydı.

It took time to realize a technological function with the multi-frame per second transition from the cinema device. Moreover, cinematic time, which reveals both the time perceived at the conscious level and the measurement of images with the concept of time in mechanical operation, has created a language of expression with the possibilities of art, science and technology for more than a century. Thus, the fluid time dimension was added to the frames emulating life and the cinematic universe was born. Subjective time imposes the movement and sensory illusion of placing meaning in the consciousness of the audience in cinema. The mechanical element that controls the fluidity of the work is the time that enables the expression to be perceived as moving. The fictional film “…Time in the first and last breath…”, which was produced to reflect the purpose and method, is based on a prediction that the innovations in technologies that emerged with the developments related to the testimony of time threaten the future of humanity. The problematic, interpreted with the lyrical approach of the film, is to emphasize that the living thing whose extinction and function is extinct is also human in the time cycle in which human-developed technologies play a role. The cardiographic chart and the straight line of death in the hospital scene, the desperation of creatures experiencing food shortages, and time-dependent meaning placement effects such as mucilage in the seas are the metaphorical style that forms the carrier axis of the film. Even though we are at the extremes of the global system, the only means of existence that does not lose its importance for cinema in the allegorical universal platform network we are on is the relatively objective critical perception of time. Cinema, the world of multi-layered processes that give strong temporal dimensions to the system we live in, has changed the technological perception of time; It would also be difficult to consider the temporality of representation. In summary, time in cinema is witnessing the ecological destruction of nature. For this reason, I wanted to express the spread of the disordered energy that emerged in the drift of the planet towards extinction in all areas of life as “Entropy in Cinema”. Because my findings should theorize new propositions about time for cinema and lead to new thoughts.
Entropy in cinema : in the post-cinematic era critical time concept
Keywords: Critical Perception of Time; Ecological Destruction; Ekolojik Yıkım Entropy in Cinema; Eleştirel Zaman Algısı; Entropi, Sinemada; Entropy in motion pictures; Post Cinema; Post-Sinema; Sinemada Entropi